2011
DOI: 10.1111/j.1365-2125.2011.03943.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐platelet therapy: cyclo‐oxygenase inhibition and the use of aspirin with particular regard to dual anti‐platelet therapy

Abstract: Aspirin and P2Y12 antagonists are commonly used anti-platelet agents. Aspirin produces its effects through inhibition of thromboxane A2 (TXA2) production, while P2Y12 antagonists attenuate the secondary responses to ADP released by activated platelets. The anti-platelet effects of aspirin and a P2Y12 antagonist are often considered to be separately additive. However, there is evidence of an overlap in effects, in that a high level of P2Y12 receptor inhibition can blunt TXA2 receptor signalling in platelets and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 139 publications
(187 reference statements)
2
164
0
Order By: Relevance
“…13 Furthermore, it has been suggested that P2Y 12 inhibition alone may partially inhibit platelet thromboxane A 2 synthesis, 14,15 and in the presence of strong P2Y 12 inhibition, the additional effects of higher aspirin doses may result in a reduction of prostacyclin release, potentially shifting the influence of aspirin to a prothrombotic effect. 16 Consistent with the Clopidogrel Optimal Loading Dose Usage to Reduce Recurrent Events/Optimal Antiplatelet Strategy for Interventions (CURRENT/OASIS 7) trial, 17 no association of aspirin maintenance dose with ischemic event rates in the clopidogrel group was observed. Further investigations in vitro and in animals and humans, and preferably prospective randomized, controlled trials, are needed to understand the role of these complex pathobiological interactions.…”
Section: Discussionmentioning
confidence: 70%
“…13 Furthermore, it has been suggested that P2Y 12 inhibition alone may partially inhibit platelet thromboxane A 2 synthesis, 14,15 and in the presence of strong P2Y 12 inhibition, the additional effects of higher aspirin doses may result in a reduction of prostacyclin release, potentially shifting the influence of aspirin to a prothrombotic effect. 16 Consistent with the Clopidogrel Optimal Loading Dose Usage to Reduce Recurrent Events/Optimal Antiplatelet Strategy for Interventions (CURRENT/OASIS 7) trial, 17 no association of aspirin maintenance dose with ischemic event rates in the clopidogrel group was observed. Further investigations in vitro and in animals and humans, and preferably prospective randomized, controlled trials, are needed to understand the role of these complex pathobiological interactions.…”
Section: Discussionmentioning
confidence: 70%
“…a well-characterized sequence of events, including the important release of secondary mediators of aggregation, notably ADP and thromboxane A 2 (1)(2)(3). These mediators are the targets of antithrombotic drugs taken by many millions of patients as prophylactic protection against heart attacks and strokes.…”
mentioning
confidence: 99%
“…A plausible mechanism was proposed for the interaction between higher aspirin dose and ticagrelor that is linked to the level of P2Y 12 inhibition and the potential prothrombotic effects of high-dose aspirin through the suppression of prostacyclin. 24,25,31,32 However, even though the study design is different, the TRial to assess Improvement in Therapeutic Outcomes by optimizing platelet inhibition with prasugrelThrombolysis In Myocardial Infarction (TRITON-TIMI) 38 study that compared the effects of prasugrel with clopidogrel showed that prasugrel reduced the risk of the composite of cardiovascular mortality, myocardial infarction, and stroke in patients with ACS scheduled for percutaneous coronary intervention, 33 irrespective of the aspirin dose. 34 Moreover, such an adverse interaction has not been reported to occur between aspirin and clopidogrel in the Clopidogrel in Unstable angina to prevent Recurrent Events (CURE) study.…”
mentioning
confidence: 99%